Understanding the financial lives of female sex workers in Abidjan, Côte d'Ivoire: implications for economic strengthening interventions for HIV prevention. (25th July 2018) - Namey, Emily; Perry, Brian; Headley, Jennifer; Yao, Albert Kouakou; Ouattara, Mariame Louise; Shighata, Coulibaly; Ferguson, Michael
ABSTRACT: Many women's decisions about whether and how to participate in sex work are driven by financial considerations. Despite the recognized importance of economic factors in HIV risk among female sex workers (FSWs), many HIV prevention programs focus narrowly on sexual risk behaviors. We collected data on the financial practices of FSWs in Abidjan, Côte d'Ivoire, to better inform economic strengthening programs for HIV risk reduction with this population. We conducted "walk-along" participant observations ( N  = 74) during FSWs' daily non-working routines and analyzed resultant notes using qualitative thematic analysis. We used a financial diary methodology to collect detailed quantitative data on income, spending, savings and lending from a sub-sample of participants ( n  = 33) over six weeks; these data were analyzed using descriptive statistics. All women in our sample reported sex work as their primary source of earned income. Median weekly income was roughly US $114, with a wide range across the sample and from week to week. Cash expenses related primarily to routine needs (e.g., food, housing, transportation) and accounted, on average, for approximately 90% of weekly spending. Around one-quarter of weekly expenses were directly associated with sex work (e.g., clothing, beauty products, and alcohol). FSWs held "savings" in boxes, mobile money platforms, informal savings groups, or banks, though most withdrew cash from these funds frequently. These findings suggest that this group of FSWs in Abidjan, Côte d'Ivoire, are not cash-poor: median weekly income is greater than the estimated Ivoirian weekly per capita gross national income. Yet the erratic nature of income alongside routine spending needs suggests that effective economic strengthening programs in this context should include financial management education, group-based savings and lending, and links to formal financial institutions. These economic strengthening activities hold promise to empower FSWs financially for downstream HIV-risk reduction benefits by building economic resilience to reduce financially-driven sexual risk decisions.